2022
DOI: 10.3390/medicina58101352
|View full text |Cite
|
Sign up to set email alerts
|

Silent Pauses and Speech Indices as Biomarkers for Primary Progressive Aphasia

Abstract: Background and Objectives: Recent studies highlight the importance of investigating biomarkers for diagnosing and classifying patients with primary progressive aphasia (PPA). Even though there is ongoing research on pathophysiological indices in this field, the use of behavioral variables, and especially speech-derived factors, has drawn little attention in the relevant literature. The present study aims to investigate the possible utility of speech-derived indices, particularly silent pauses, as biomarkers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 68 publications
4
26
1
Order By: Relevance
“…As is visible in Figure 4A, the speech rate was significantly reduced compared to controls in more than half the papers for all patient groups except ALS-FTD. However, the Greek patient populations with mxPPA, lvPPA, and svPPA had no significant reduction in speech rate (Karpathiou & Kambanaros, 2022; Potagas et al, 2022). Some English patient populations with lvPPA, svPPA, and bvFTD also had no significant differences in speech rate (Ash et al, 2013; Bird et al, 2000; Mack et al, 2015; Marcotte et al, 2017; Pressman et al, 2019; Rohrer & Warren, 2010; Sajjadi et al, 2012; Thompson, 2012; Wilson et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As is visible in Figure 4A, the speech rate was significantly reduced compared to controls in more than half the papers for all patient groups except ALS-FTD. However, the Greek patient populations with mxPPA, lvPPA, and svPPA had no significant reduction in speech rate (Karpathiou & Kambanaros, 2022; Potagas et al, 2022). Some English patient populations with lvPPA, svPPA, and bvFTD also had no significant differences in speech rate (Ash et al, 2013; Bird et al, 2000; Mack et al, 2015; Marcotte et al, 2017; Pressman et al, 2019; Rohrer & Warren, 2010; Sajjadi et al, 2012; Thompson, 2012; Wilson et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…76 papers studying discourse in patients with FTD were included in the final review. 57 of these papers (75% of all papers) studied English-speaking patients, the remaining 19 papers studied patients speaking Spanish (Baque et al, 2022; Matias-Guiu et al, 2020, 2022), Czech (Daoudi et al, 2022; Rusz et al, 2015; Skrabal et al, 2020), Italian (Catricala et al, 2019; Silveri et al, 2014), French (Bouvier et al, 2021; Macoir et al, 2021), German (Hohlbaum et al, 2018; Staiger A., 2017), Dutch (Bruffaerts et al, 2022), Greek (Karpathiou & Kambanaros, 2022; Koukoulioti et al, 2018, 2020; Potagas et al, 2022), Hindi (Sachin et al, 2008), and Korean (Suh et al, 2010) (Figure 2a). Figure 2b shows the geographical representation of the published papers, with a paucity of languages from South America, Asia, and Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Mignard et al [ 50 ] investigated fluency disorders in Parkinson’s patients by the pause ratio. Potagas et al [ 51 ] used speech rate, articulation rate, pause frequency, and pause duration as analytical indicators, and the results showed that silent pauses can be used as complementary biomarkers for PPA. Imre et al [ 52 ] conducted a study on the temporal speech characteristics of elderly patients with type 2 diabetes (T2DM).…”
Section: Discussionmentioning
confidence: 99%
“…They provide objective, reliable measures of fluency at the speech production level that could be part of the multidimensional fluency profiles that are called for in the domain. The automatic estimates of speech rate and of the number of silent or filled pauses they rely on are also used for assessing fluency in PWA (Gordon & Clough, 2022;Wang et al, 2013), with some of these indicators also being used for classifying subtypes of aphasia (Ash et al, 2013;Fraser et al, 2014;Potagas et al, 2022). Moreover, as they only process speech signals in the temporal domain, the algorithms require very low computing resources, which make their execution on standard PCs very rapid.…”
Section: Introductionmentioning
confidence: 99%